Prognostic value of nasal cytology and clinical factors in nasal polyps development in patients at risk: can the beginning predict the end?. Issue 9 (30th June 2017) - De Corso, Eugenio; Lucidi, Daniela; Battista, Mariapina; Romanello, Matteo; De Vita, Carla; Baroni, Silvia; Autilio, Chiara; Galli, Jacopo; Paludetti, Gaetano
Abstract : Background: We evaluated the prognostic value of nasal cytology and clinical factors in predicting nasal polyp (NP) development in patients with history of nonallergic chronic sinonasal inflammation. Methods: This was a retrospective case‐control study of 295 patients followed at our institution for a mean of 85.70 ± 19.41 months. According to the inclusion criteria we enrolled 84 cases with persistent eosinophilic nonallergic sinonasal inflammation (group A) and 106 cases with neutrophilic inflammation (group B), both without evidence of NPs at the baseline. We considered as controls 105 patients affected by nonallergic noninfectious vasomotor rhinitis without evidence of inflammation at nasal cytology (group C). Patients were checked every 6 months for NPs. Temporal analyses was performed by Kaplan‐Mayer curves and odds ratios were evaluated by logistic regression analyses. Results: The percentage of patients that developed NPs was higher in group A (29/84 [34.52%]) than in group B (17/106 [16.03%]) and group C (5/104 [4.7%]) ( p < 0.05). Logistic regression analyses showed that eosinophilic patients had a higher risk of NP development over the years than neutrophilic patients compared to controls (odds ratio [OR], 10.55 vs 3.2). We also demonstrated that hypereosinophilia, asthma, and aspirin intolerance may increase the OR differently in eosinophilic patients. Conclusion: Our data suggest that early identification of inflammatory patterns and associated clinical factors in patients affected by chronic nonallergic sinonasal inflammation have a prognostic value that can help to identify patients with different risks of NP development. Our data confirm that detection of nasal eosinophilic inflammation represents an early marker for identification of a more aggressive inflammatory phenotype.